The Effect of Abusive Supervision on Safety Behaviour: A Moderated Mediation Model - Xinyong Zhang (MDPI AG, 2021)
Leadership behavior has an impact on the behavior of employees. Previous studies have mainly studied the impact of positive leadership behaviors on employees’ behaviors, but there is an absence of research on the impact of negative leadership behaviours (abusive supervision) on safety behaviours (including safety participation and safety compliance). In this study, 599 front-line employees in the petrochemical industry were selected as subjects. Abusive supervision, safety behaviour, safety motivation and a conscientiousness questionnaire were used as measurements to explore the relationship between abusive supervision and employee safety behaviors, and to further explore the roles of safety motivation, conscientiousness and the relationship between them. This study found that abusive supervision is negatively related to employee safety behaviours (safety compliance and safety participation); that safety motivation plays a mediating role in the relationship between abusive supervision and employees’ safety behavior; and that conscientiousness moderates the role of safety motivation between the relationship of abusive supervision and employees’ safety behaviour. With a higher level of conscientiousness, the indirect relationship between abusive supervision and employee safety behaviours is weaker. Finally, we discuss the theoretical and practical significance of these findings for abusive supervision and the management of safety behaviours.